Failure Analysis Fundamentals and Applications in Mechanical Components - Otegui, Jose Luis (Springer International Publishing : Imprint: Springer, 2014)
This book addresses the failures of structural elements, i.e. those components whose primary mission is to withstand mechanical loads. The book is intended as a self-contained source for those with different technical grades, engineers and scientists but also technicians in the field can benefit from its reading.